The concept of civilization at Ibn Khaldun and its dimensions - AISSAOUA, Wahiba (Social Sciences Journal)
Introduction: We cannot talk about the concept of urbanization and civilization according to Ibn Khaldun without talking about the civilizational struggle that is taking place today, and which our nation is experiencing with full force.